Corporate sustainability disclosure and firm value in Malaysia: Role of ownership structure / Anas Abd Rasid - Anas , Abd Rasid (2023)
Malaysia has embarked into the journey of sustainability many years ago, notably since the inception of United National Sustainability Development Goal (UNSDG). Among many measures undertaken and supported by the government to put forward the sustainability agenda, corporate sustainability is one of the key emphasis in the national development. This is evident by initiatives such as the introduction of Bursa Malaysia FTSE 4 Good Index, Socially Responsible Investment (SRI) Framework by Securities Commissions and the National Annual Corporate Reporting Awards (NACRA). One of the biggest milestone achieved by corporate Malaysia is the introduction of Bursa Malaysia Sustainability Reporting Guide in 2015, in line with the mandatory requirement of sustainability reporting imposed on public listed companies starting 2016. Motivated by the new development of sustainability reporting in Malaysia and wide interest among researchers on the nexus between sustainability reporting and its impact on firm performance, this study examines the relationship between sustainability reporting disclosure level and firm performance. Considering the unique structure of ownership and its potential impact on disclosure level and firm performance, this study also includes two types of ownership that are fairly common in corporate Malaysia; concentrated ownership and government ownership as moderators. In this study, a total of 495 firm-year observations are selected as samples ranging from the year 2016 to 2020 in Malaysia. This is to ensure the samples selected conform with the mandatory requirement of reporting in Malaysia and in addition to obtain a balanced panel data, which is central to the method employed in this study. A conceptual framework is constructed for this study, built on the premise of stakeholders theory to explain the relationship between sustainability reporting disclosure level and firm performance. Our findings show that in there is a significant relationship between sustainability reporting disclosure level and firm performance in Malaysian firms. In addition, our study also concludes that government ownership moderates the relationship between sustainability reporting disclosure level and firm performance at 10% significance level. As for concentrated ownership, it negatively moderates the relationship between sustainability reporting disclosure level and firm performance. Consistent with two recent past studies conducted in Malaysia, the number of years under observation are considered relatively on the shorter range whilst it is believed that longer time is needed for performance improvement and value creation to be reflected as a result of sustainability practices. This study contributes to the academic research fraternity, regulatory environment as well as the industry players. From academic perspective, it contributes by adding to the body of knowledge, a new set of findings conducted in Malaysia. To our best knowledge, this is also a pioneer study that included ownership structure as moderator to the nexus between corporate sustainability reporting disclosure level and firm performance in Malaysia. On top of that, it also provides information to the regulator as to the impact of the recently regulated mandatory reporting requirement on the firms affected. For the industry players, it demonstrates to them the impact of their sustainability practices on creating improved performance for their companies so far. Nevertheless, the study also identified some limitations. This includes the relatively shorter timeframe, unstandardised scoring method compared to past studies and absence of industry based analysis. This limitations is considered to form suggestions to be addressed in future research